Effect of plant extract against opportunist human pathogen soil bacteria - Tóth, Csaba Tamás; Csubák, Mária (Acta Agraria Debreceniensis, 2012)
Our experiments have repeatedly shown that the extract of ragweed (Ambrosia artemisiifolia) is an antifungal and antibacterial component. In our paper we tested of the biological activity of the herbal substance against opportunistic human pathogenic bacteria strains (Staphylococcus aureus 110003 and 25923; Staphylococcus saprophyticus 110008). Our laboratory tests show that the extract is bacteriostatic and in several cases bactericid. We can assume that from the the agricultural and public health aspects can be extremely dangerous weed, contains biologically active components and it may be suitable for the prepare of antibacterial agents.